Bi-dimensional acculturation and depressive symptom trajectories from pregnancy to 1 year postpartum in marriage-based immigrant women in Taiwan. Issue 12 (2nd December 2020) - Chen, Hung-Hui; Lai, Jerry Cheng-Yen; Hwang, Fang-Ming; Chien, Li-Yin
Abstract: Background: Childbirth may pose many challenges to the psychological well-being of marriage-based immigrant mothers in interracial marriages, who must negotiate bi-dimensional acculturation – adaptation to the host culture and maintenance of her own heritage culture. We examined the temporal relationships between bi-dimensional acculturation and depressive symptoms from pregnancy to 1 year postpartum among marriage-based immigrant mothers in Taiwan using the cross-lagged structural equation modeling. Methods: This study recruited 310 immigrant mothers, who were examined in the second and third trimesters, and again at 1 month, 3 months, 6 months, and 1 year postpartum from March 2013 to December 2015. Depressive symptoms and bi-dimensional acculturation were measured using the Edinburgh Postnatal Depression Scale and Bidimensional Acculturation Scale for Marriage-Based Immigrant Women, respectively. Results: The study found that adaptation to the host culture followed a downward linear trajectory, while maintenance of the mother's own heritage culture followed an upward linear trajectory from pregnancy to 1 year postpartum. All but one cross-lagged path between bi-dimensional acculturation and depressive symptoms was statistically insignificant, though almost all cross-sectional associations were significant. Adaptation to host culture was negatively associated with depressive symptoms at all time points. The association between maintenance of heritage culture and depressive symptoms reversed from positive to negative after 6 months postpartum. Conclusions: Adaptation to the host culture and maintenance of the mother's heritage culture differed in their associations with maternal depressive symptoms. Health professionals should assist immigrant mothers in adapting to the host culture while supporting their heritage culture in the childbearing period.